2003
DOI: 10.1017/s1461145703003778
|View full text |Cite
|
Sign up to set email alerts
|

Possible relationship between mitochondrial DNA polymorphisms and lithium response in bipolar disorder

Abstract: Although many investigators have been searching for genetic markers to predict lithium response in bipolar disorders, no genetic predictor has been established yet. We previously reported the association of mitochondrial DNA (mtDNA) 5178 and 10398 polymorphisms with bipolar disorder. The objective of this study is to clarify whether these mtDNA polymorphisms can predict response to maintenance lithium treatment in bipolar patients. We examined these polymorphisms and some clinical variables in 54 bipolar patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…They reported a significant association between the C5178A polymorphism and extraversion in healthy controls (n = 238). A separate study suggested the mtDNA A10398G polymorphism of the MT-ND3 genes may be related to lithium response in BPD (90).…”
Section: Munakata Et Al (2005)mentioning
confidence: 99%
“…They reported a significant association between the C5178A polymorphism and extraversion in healthy controls (n = 238). A separate study suggested the mtDNA A10398G polymorphism of the MT-ND3 genes may be related to lithium response in BPD (90).…”
Section: Munakata Et Al (2005)mentioning
confidence: 99%
“…29 The cornerstone of the GABA hypothesis of bipolar disorder is that GABA provides an inhibitory action to both norepinephrine and dopamine systems. 30 Although this widely expressed neurotransmitter has been thought to exert a tonic inhibitory effect on norepinephrine systems, an earlier study 31 suggests that GABA may in fact facilitate norepinephrine activity. It also reported that plasma GABA levels are relatively reduced in depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among those candidate genes, the tryptophan hydroxylase C allele (TPH), 73 the phospholipase C g-1 gene (PLCG1) repeat, 74,75 the C973A polymorphism in the inositol polyphosphate 1-phosphatase 76 and the mitochondrial DNA (mtDNA) 10398 polymorphism, 77 have been suggested as being associated with positive lithium response.…”
Section: Discussionmentioning
confidence: 99%